Some questions about the state of the eye surface in patients before cataract surgery - N. S. Lutsenko; O. A. Isakova; O. A. Rudycheva; T. S. Kyrilova; T. S. Mihalchik (Сучасні медичні технології, 2020)
Introduction. Ocular surface status is a main risk factor for the development of postoperative complications and lead to the decrease of life quality.